2011
DOI: 10.1074/jbc.m111.254003
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Digoxin That Antagonizes RORγt Receptor Activity and Suppresses Th17 Cell Differentiation and Interleukin (IL)-17 Production

Abstract: The retinoic acid-related orphan nuclear receptor ␥t (ROR␥t)/ROR␥2 is well known as a master regulator of interleukin 17 (IL-17)-producing helper T (Th17) cell development. To develop a therapeutic agent against Th17-mediated autoimmune diseases, we screened chemical compounds and successfully found that digoxin inhibited IL-17 production. Further studies revealed that digoxin bound to the ligand binding domain of ROR␥t and suppressed Th17 differentiation without affecting Th1 differentiation. To better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
111
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 47 publications
4
111
1
Order By: Relevance
“…This implies that RORs contain an activation function (AF-2) located at the C terminus of its LBD, and agonist binding induces the AF-2 helix to adopt a conformation that encourages interactions with the LXXLL motifs of co-activator proteins such as SRCs (Fujita-Sato et al, 2011; Jin et al, 2010; Kurebayashi et al, 2004). On the basis of the results from two-hybrid assay, we showed that the LBDs of RORα and RORγ can interact with the LXXLL motifs of EBIP96 even in the absence of any exogenous ligands (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that RORs contain an activation function (AF-2) located at the C terminus of its LBD, and agonist binding induces the AF-2 helix to adopt a conformation that encourages interactions with the LXXLL motifs of co-activator proteins such as SRCs (Fujita-Sato et al, 2011; Jin et al, 2010; Kurebayashi et al, 2004). On the basis of the results from two-hybrid assay, we showed that the LBDs of RORα and RORγ can interact with the LXXLL motifs of EBIP96 even in the absence of any exogenous ligands (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the up-regulation of Arrb1 expression in T H 17 cell differentiation was inhibited by Digoxin (Fig. 5B), a RORγt-specific inhibitor in T H 17 cells (26,27). Further investigation is needed for clarification of β-arrestin1 expression regulated by RORγt.…”
Section: Ccr6mentioning
confidence: 99%
“…Surprisingly, recent studies ascertained that digoxin and its derivatives can inhibit Th17 cell differentiation and IL-17A production by selectively antagonizing the activity of RORγt. 24,25 In an experimental autoimmune encephalomyelitis model, which is a canonical IL-17A-mediated autoimmune disease model, digoxin conspicuously inhibits IL-17A production, attenuating the severity of experimental autoimmune encephalomyelitis. …”
mentioning
confidence: 99%
“…24,25 In an experimental autoimmune encephalomyelitis model, which is a canonical IL-17A-mediated autoimmune disease model, digoxin conspicuously inhibits IL-17A production, attenuating the severity of experimental autoimmune encephalomyelitis. 24 In our previous study, we found that digoxin significantly prolonged allograft survival time in the BALB/cto-B6 mouse cardiac transplantation model by suppressing Th17 cell differentiation. 26 However, it is unknown whether the specific RORγt antagonist could attenuate experimental AAA (EAAA).…”
mentioning
confidence: 99%